Imperfect Corrections or Correct Imperfections?: Psychometric Corrections in Meta-Analysis – ADDENDUM. Issue 2 (28th July 2015) - Oswald, Frederick L.; Ercan, Seydahmet; McAbee, Samuel T.; Ock, Jisoo; Shaw, Amy
<x content-type="archive" xml:space="preserve">Abstract</x> In Industrial and Organizational Psychology volume 7, issue 4, a commentary to the focal article Oswald et al.1 was unfortunately omitted. This commentary, "Imperfect Corrections or Correct Imperfections? Psychometric Corrections in Meta-Analysis, " by Frederick L. Oswald, Seydahmet Ercan, Samuel T. McAbee, Jisoo Ock, and Amy Shaw, 2 is reproduced in the following pages.